Inventory of trees in tropical dry deciduous forests of Tiruvannamalai district, Tamil Nadu, India - DURAI SANJAY GANDHI; SOMAIAH SUNDARAPANDIAN (Biodiversitas Journal of Biological Diversity, 2014)
Sanjay-Gandhi D, Sundarapandian S. 2014. Inventory of trees in tropical dry deciduous forests of Tiruvannamalai district, Tamil Nadu, India. Biodiversitas 15: 169-179. Diversity and distribution patterns of tree species were inventoried in 20 one hectare plots in SathanurReserve Forest of Tiruvannamalai district, Tamil Nadu, India. These plots were grouped into three sites based on their location in thereserve forest and the level of disturbance. Site I (8 plots) near to the road and agricultural lands, Site II (8 plots) away from the road andhuman settlements and site III (4 plots) along the canal-side where the terrain contain rocks here and there. A total of 60 speciesbelonging to 48 genera and 29 families were enumerated including 13,412 stems (â‰¥3.2cm DBH size class). The species richness in thestand (plot) varied from 7 ha-1 to 28 ha-1 and the stand density varied from 336 ha-1 to 1075 ha-1. Albizia amara (7999) was the dominantspecies in terms of density, basal area and IVI in all the study plots except plot no.16, where Chloroxylon swietenia was dominantindicates a mono-species dominated forest ecosystem. The mean values of Shannon and dominance indices were 1.406 and 0.411respectively. Diameter class-wise distribution showed L-shaped curve, a sign of good regeneration status. Cattle grazing and illegal fuelwood collection have been observed to pose huge pressure to the integrity of this tropical dry forest, still it have substantial tree speciesdiversity similar to many other dry forests in India and elsewhere.